Examining Associations Between Child Abuse and Neglect Experiences With Emotion Regulation Difficulties Indicative of Adolescent Suicidal Ideation Risk - Hatkevich, Claire; Sumlin, Eric; Sharp, Carla (Frontiers in Psychiatry, 2021)
Objective: Preliminary work indicates one specific aspect of emotion dysregulation (i.e. limited access to emotion regulation strategies) uniquely associates with adolescent suicide ideation. An optimal score cut point on a measure of this emotion dysregulation impairment has been identified to indicate risk for past-year suicidal ideation. Examining types of child abuse and neglect associated with being above cut-off on this measure may point to interactive environmental effects associated with subsequent risk for suicidal ideation. The primary aim of this study was to investigate the relations between multiple types of child abuse and neglect with being above cutoff on a measure of limited access to emotion regulation strategies in a psychiatrically severe adolescent sample. Method: The full sample included 203 psychiatric adolescents (Mean age = 15.31 years; 66.5% female; 74.4% White), assigned to two groups: 1) those at or above cutoff on the access to emotion regulation strategies subscale (n = 139); and 2) those below cutoff (n = 64). Results: Significant differences were only evidenced between the emotion regulation cutoff groups on emotional abuse, after covarying for other types of abuse and neglect; significant group differences were not evidenced on any other type of abuse or neglect (sexual or physical abuse, emotional or physical neglect). Conclusion: Relative to other types of abuse and neglect, emotional abuse may be differentially related to experiencing limited access to emotion regulation strategies, at the level indicative of suicide ideation risk. Clinical implications are discussed.